Evaluation of a shared pharmacogenomics curriculum for pharmacy students. (March 2015) - Lee, Kelly C; Hudmon, Karen Suchanek; Ma, Joseph D; Kuo, Grace M
Aim: This national dissemination study evaluated pharmacy students' self-reported overall ability, self-efficacy and attitudes toward applying pharmacogenomics and perceptions of Pharmacogenomics Education Program, a shared pharmacogenomics curriculum.Patients & methods: Following a series of train-the-trainer programs for pharmacy faculty, pre- (n = 2674) and post-training surveys (n = 2542) were administered to Doctor of Pharmacy students (n = 43 pharmacy schools).Results: Students reported increased (pre- vs post-training) overall ability to educate patients about pharmacogenomics (17 vs 63%; p < 0.0001) and pharmacogenomic testing (11 vs 60%; p < 0.0001) and increased self-efficacy for identifying therapeutic areas for which pharmacogenomic testing is required (20 vs 75%; p < 0.0001). Most (92%) agreed that students at other schools would benefit from receiving the same, or similar, pharmacogenomics education.Conclusion: A shared curriculum is an effective approach for broadscale curricular dissemination. Original submitted 17 October 2014; Revision submitted 19 December 2014